2022
DOI: 10.1002/jcla.24386
|View full text |Cite
|
Sign up to set email alerts
|

The preventive effects of different doses of atorvastatin on contrast‐induced acute kidney injury after CT perfusion

Abstract: Background: Contrast-induced acute kidney injury (CI-AKI) is a severe complication among patients receiving intravascular contrast media. The purpose of this study was to investigate the preventive effects of pretreatment of atorvastatin at intensive doses on CI-AKI after computed tomography (CT) perfusion. Methods:The levels of serum creatinine (SCR), blood urea nitrogen (BUN), Cystatin C (CysC), estimated glomerular filtration rate (eGFR), high-sensitivity C-reactive protein (hs-CRP), and interleukin-6 (IL-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…It was found that the sensitivity of CysC for diagnosing renal insufficiency was 82.8%, while that of Scr was only 68.2%, thus CysC is easier to detect. Therefore, as a marker of kidney function, CysC is more ideal than Scr [ 52 , 53 ]. Finally, a recent publication stated that sCysC at 24 h was the best biomarker for CIN diagnosis, while baseline levels of other common biomarkers were the best predictors of prognosis [ 54 ].…”
Section: Novel Biomarkers: the Necessity For A Precise Ci-aki Diagnosismentioning
confidence: 99%
“…It was found that the sensitivity of CysC for diagnosing renal insufficiency was 82.8%, while that of Scr was only 68.2%, thus CysC is easier to detect. Therefore, as a marker of kidney function, CysC is more ideal than Scr [ 52 , 53 ]. Finally, a recent publication stated that sCysC at 24 h was the best biomarker for CIN diagnosis, while baseline levels of other common biomarkers were the best predictors of prognosis [ 54 ].…”
Section: Novel Biomarkers: the Necessity For A Precise Ci-aki Diagnosismentioning
confidence: 99%
“…The protective effect of atorvastatin on CIAKI depends on the dose. [14][15] But high dose of statins have side effects such as myolysis and liver damage, so we need to combine some drug with atorvastatin to prevent CIAKI. Both clinical studies [16][17][18][19][20] and animal experiments [21][22] have demonstrated that probucol or alprostadil can reduce renal damage by contrast agents and reduce the incidence of CIAKI.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is a costly procedure, which poses an increased economic burden on patients and reduces their quality of life. Thus, CI-AKI prevention finds profound significance (4).…”
Section: Introductionmentioning
confidence: 99%